Image Operations: Visual Media and Political Conflict - Eder, Jens and Klonk, Charlotte. (Manchester University Press, 2016)
A powerful book that provides new interdisciplinary perspective on the functions of still and moving images in political conflict.
https://katalog.adlr.link/Record/76-EBC4786642